A Case Study on Consumer Buying Behavior towards Selected FMCG Products (International Journal of Scientific Research and Management (IJSRM), 2017)
The consumer behaviour plays an important role in marketing of fast moving consumer goods.This behaviour is effected by various factors.In the present era of globalisation needs and wants of consumers changes with time.The fast moving consumer goods (FMCG) sector contributes a lot to the growth of India’s GDP.Therefore it is neccesary to identify the changes in consumer buying behaviour towards FMCG products.The motive of this paper is to identify the factors affecting consumer buying behviour towards FMCG products and finally effecting their decision making process.The data for this study has been collected through questionnaire and findings have been theoretically presented.The paper reveals that consumer behaviour is largely effected by place,product,price,promotion,physiological and pshycological factors.However effect of these factors also differ from product to product.